How South Korea’s Soft Power Reversed Global Student Mobility - Kim, Kyuseok; Kim, Najung (International Higher Education, 2025)
<h3 id="south-korea-has-rapidly-emerged-as-a-top-destination-for-international-students-reversing-long-standing-patterns-of-outbound-mobility-fueled-by-the-global-reach-of-k-culture-this-transformation-reflects-a-unique-soft-power-strategy-that-differs-from-those-of-its-regional-neighbors-while-japans-cultural-influence-remains-rooted-in-long-established-media-forms-and-china-emphasizes-economic-and-political-investment-south-koreas-strength-lies-in-its-ability-to-convert-popular-culture-into-educational-aspiration" data-pm-slice="1 1 []">South Korea has rapidly emerged as a top destination for international students, reversing long-standing patterns of outbound mobility. Fueled by the global reach of K-Culture, this transformation reflects a unique soft power strategy that differs from those of its regional neighbors. While Japan’s cultural influence remains rooted in long-established media forms and China emphasizes economic and political investment, South Korea’s strength lies in its ability to convert popular culture into educational aspiration.